1994
DOI: 10.1093/nar/22.11.1954
|View full text |Cite
|
Sign up to set email alerts
|

An intervening sequence (IVS) in the 16S rRNA gene of the eubacteriumHelicobacter canis

Abstract: PCR amplicons enlarged by approximately 250bp were generated from the 16S rRNA (rrs) genes of certain strains of the recently described Helicobacter species, H. canis. The DNA sequence of the rrs gene of one such strain was determined, and it was shown that an intervening sequence (IVS) of 235bp followed nucleotide 199 in the rrs sequence. In four other H. canis strains, identical or similar IVSs were found, always at the same location in the rrs gene. The secondary structures of the RNA transcripts of the IVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
(20 reference statements)
6
30
0
Order By: Relevance
“…Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7). In this study, we also showed that true selfsplicing introns can be present in bacterial 16S rRNA genes, leading to the conclusion that the 16S rRNA genes of bacteria can indeed be far longer than ∼1,500 nucleotides.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7). In this study, we also showed that true selfsplicing introns can be present in bacterial 16S rRNA genes, leading to the conclusion that the 16S rRNA genes of bacteria can indeed be far longer than ∼1,500 nucleotides.…”
Section: Discussionsupporting
confidence: 53%
“…The possibility that the 16S rRNA gene may not have a conserved size has not been sufficiently considered in designing and applying techniques for diversity studies, even though elongations of 16S rRNA genes due to intervening sequences have been reported before (3)(4)(5)(6)(7). Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 5), suggesting variation between rrn copies within a genome. Variation in the length of 23s rDNA and 16s rDNA between strains within species has been reported previously and has been shown to result from the presence of intervening sequences [27]. The results of the present study suggest the presence of variant rrn operons within the genomes of some H. inJuenzae strains.…”
Section: Ribotyping Of H Influenzaesupporting
confidence: 80%
“…The presence of IVS within rRNA genes has previously been reported for several bacterial genera of other phylogenetic groupings. IVS were, for example, re- ported in the 23S rDNA of Haemophilus (Song et al, 1999), Salmonella (Pabbaraju & Sanderson, 2000) and Leptospira (Ralph & McClelland, 1993) and in the 16S rDNA of Helicobacter (Linton et al, 1994) and ' Candidatus Blochmannia ' (Sauer et al, 2000). The highly variable extended stem-loop structures formed by the IVS are excised from the rRNA post-transcriptionally (Burgin et al, 1990).…”
Section: S and 23s Rdna-based Phylogeny Of Bacterial Endosymbiontsmentioning
confidence: 99%